2018
DOI: 10.2340/16501977-2326
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometry: A feasible method to monitor physical activity during sub-acute rehabilitation of persons with stroke

Abstract: Objective: To investigate the feasibility of using accelerometers to monitor physical activity in persons with stroke admitted to inpatient rehabilitation. Design: Longitudinal observational study. Participants: Persons with stroke admitted to a specialized rehabilitation centre for sub-acute rehabilitation were recruited between August and December 2016. Methods: Volume and intensity of physical activity were assessed with accelerometers throughout the rehabilitation period. Indicators of feasibility included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 37 publications
0
19
0
2
Order By: Relevance
“…In line with our findings, previous literature affirms that physical factors, gait and balance control, impact on stroke survivors' ability to participate in PA. 12 Our findings corroborate with previous studies in the subacute phase demonstrating that stroke survivors with a gait speed of approximately ≥0.9 m/s took more steps per day and spent more time in MVPA than survivors with more severe walking limitations. 34,35 We further deducted that even the community ambulation group in our study had a lower PA level (3524 steps/day) compared to previous observations of chronic stroke survivors in more developed countries (4078 steps/day). 7 We believe that the contextual setting where the present study was situated, areas of Figure 1.…”
Section: Discussionmentioning
confidence: 43%
“…In line with our findings, previous literature affirms that physical factors, gait and balance control, impact on stroke survivors' ability to participate in PA. 12 Our findings corroborate with previous studies in the subacute phase demonstrating that stroke survivors with a gait speed of approximately ≥0.9 m/s took more steps per day and spent more time in MVPA than survivors with more severe walking limitations. 34,35 We further deducted that even the community ambulation group in our study had a lower PA level (3524 steps/day) compared to previous observations of chronic stroke survivors in more developed countries (4078 steps/day). 7 We believe that the contextual setting where the present study was situated, areas of Figure 1.…”
Section: Discussionmentioning
confidence: 43%
“…Step counters have been identified as a useful device for measuring the mobility of post-stroke patients in an ecological way [15]. Even though some authors have demonstrated the possibility of quantifying the level of activity and gait pattern of healthy subjects with a single wearable sensor, this functionality has yet to be confirmed in stroke patients [25]. The quantification of stroke mobility is a new and very important concept because changes in steps per day seem to strongly influence health and global functioning outcomes [13].…”
Section: Discussionmentioning
confidence: 99%
“…Step counters can be used to detect post-stroke patients' activity levels [25][26][27], assess gait and balance parameters [28,29], and guide the patients in performing exercises [30], as well as acting as a stimulus to increase in-and out-patient activity levels [14]. The literature shows that the monitoring of patients' mobility in an inpatient setting can give information similar to advanced and time-consuming techniques, such as behavioral mapping, and it can be useful to collect the activity levels of hospitalized patients [31].…”
Section: Introductionmentioning
confidence: 99%
“…Connected medication dispensing unit (Brath et al, 2013;Forni Ogna et al, 2013) Biometric tracking Blood pressure Wireless blood pressure cuff/Bluetooth to Smartphone application (Ciemins et al, 2018;Evans et al, 2016) Weight Digital weight scale (Demiris et al, 2013) Body temperature Digital thermometer (Ask, Ekstrand, Hult, Lindén, & Pettersson, 2012) Oxygen saturation Wireless pulse oximeter (Velardo et al, 2017) Blood glucose level Digital glucose monitor (Lee et al, 2017) Lung function Digital spirometer (Shakkottai, Kaciroti, Kasmikha, & Nasr, 2018) Heart rate Wrist-worn activity tracking device (Thiebaud et al, 2018) Behavioral tracking Activity level Pedometer watch/Accelerometer (Actigraph) (Hooke, Gilchrist, Tanner, Hart, & Withycombe, 2016;Joseph, Stromback, Hagstromer, & Conradsson, 2018) Calorie burning Fitness tracker with calorie burning calculator (Franco, Fallaize, Lovegrove, & Hwang, 2016) Sleep quality Bed sensor strip with ballistocardiography sensor (Kortelainen, van Gils, & Pärkkä, 2012) Daily hygiene routine Water sensors, motion sensors (J. Chung et al, 2017) Environmental tracking Room temperature Temperature sensor (Bock et al, 2016) Noise Indoor sound level sensor (Risojević , Rozman, Pilipović, Češnovar, & Bulić, 2018) Luminosity Home digital luminosity sensor (Bock et al, 2016) Humidity Indoor air quality sensor (Bock et al, 2016) Social interactions tracking Number of visitors Door sensor (Skubic, Guevara, & Rantz, 2015) Time spent outside the home…”
Section: Medication Adherencementioning
confidence: 99%